A study of the removal of some toxic metals In tap water by coffee grounds - Rahman, Sharifah Nur Hafiza Syed A (Universiti Sains Malaysia, 2006)
This research is a study about the removal of toxic metals such as iron and chromium in tap water using coffee grounds as filters. Three samples of tap waters from different areas were collected, one sample from HUSM, one from Nurani Hostel and another one from D'Village (restaurant outside the campus). The purpose of collecting water samples from different areas is to determine whether the water from different tap water sources have different concentration of the metals concerned. Three different types of commercial coffee brands were selected to constitute different thickness of the coffee bed which were composed of fine, medium and coarse particles. This is to study the relevance of the coffee texture in the removal of the metals and the reason for selection of a variety thickness of coffee beds is to investigate the significance of the coffee bed thickness in the removal of metals. In the preparation of coffee, equal amounts of different types of coffee grounds were allowed to be in contact with different type of water, maintaining a constant time in which the coffee is in contact with water. In the first step, the concentration of the chromium and iron in the three samples of water was determined using the Atomic Absorption Spectrometry (AAS). The concentration of metals in the tap water samples were found to be very low, especially chromium. Therefore, the water samples had to be acid digested, complexed with a chelating agent and extracted by methyl isobutyl ketone (MIBK) to give a higher concentration of the metals. After the concentration of the metals in water samples were obtained, coffee was prepared using water from the same samples. As three different types of coffee were used and along with three different sources of water, a total of nine coffee extracts were prepared. The coffee extracts were oxidized first to remove the organic matter. Concentration of total iron was determined by direct AAS while that of chromium was estimated after MIBK treatment.